The Influence of Stub Length and Texture of Pruning Wound Surface on the Wound Occlusion (Case Study on Tree Healt at the Mataram University Campus) - Suripto; Lalu Muhammad Aby Dujana; Rachmawati Noviana Rahayu; Supardiono (Postgraduate, University of Mataram, 2026)
Improper tree pruning, such as leaving long stubs and rough pruning wounds often leads to tree health problems in the form of poor wound occulision. This study aimed to determine the effect of stub length and pruning wound texture on wound occlusion. Stub length was measured in cm, wound texture was scored as 0 if rough and 1 if smooth, and wound occlusion was measured as the % of wound surface area covered. The influence of stub length and wound texture was tested using regression analysis. The results showed that on short stubs (4-12 cm), smooth wounds produced good to very good occlusion, while rough wounds produced poor occlusion. As the stub length increases to 14–35 cm (medium stub), smooth wounds still produced rather to good occlusion. On long stubs (40-100 cm), maximum occlusion was only rather good and predominantly poor. In very long stubs (>100 cm), occlusion was consistently poor to very poor, regardless of wound texture. Stub length and wound texture significantly influence wound occlusion with the model Y = 57.7283 -0.44X1 +13.03X2. To achieve good occlusion (>65%), the remaining stub length should be <14 cm with a smooth pruning wound.